Frequency and Risk Factors of Diabetic Complications among Selected Group of Diabetic Patients: Real-life Scenario from a Developing Country, Bangladesh - Haque, Hasna Fahmima; Afroz, Farhana; Afroze, Samira Rahat; Mitra, Palash; Rahim, Muhammad Abdur; Ahmed, AKM Shaheen; Musa, AKM (BIRDEM Medical Journal, 2017)
Background: Diabetes mellitus is a major global public health problem and its complications like coronary artery disease (CAD), stroke, amputations, nephropathy and retinopathy are alarming public health issues. These complications result in significant morbidity, mortality and huge economic burden for the patient and society. This current study aimed to evaluate the frequency of different diabetic complications and their risk factors in a real-life setting. Methods: This cross-sectional study was done in BIRDEM General Hospital from July to December 2015. Diagnosed adult diabetic patients of either sex irrespective of duration and type of diabetes were consecutively and purposively included in this study. Enrolled patients were evaluated clinically and by laboratory investigation. Results: Total patients were 400 with female predominance (57.8%). Mean age was 54.5±10.9 years. Majority (57.5%) were from urban areas, 82% had hypertension and 37.5% had dyslipidaemia. Mean duration of diabetes was 11.6±7.6 years, mean body mass index was 24.6±4.5 kg/m2, mean HbA1c was 9.1±2.0%. Nephopathy (42.5%) was the commonest complication followed by retinopathy (37.8%), neuropathy (29.8%), CAD (25.8%), peripheral vascular disease (14%) and stroke (11%). Long duration (?5 yrs) and poor control of diabetes (HbA1c?7%), family history of diabetes, hypertension, dyslipidaemia and male sex were significant risk factors for diabetic complications. Conclusions: Complications of diabetes are common. Glycaemic control and control of hypertension, dyslipidaemia and weight management may halt or delay the development of complications of diabetes. Patient education is of paramount importance in this regard. Birdem Med J 2017; 7(2): 143-147